2016
DOI: 10.1186/s12915-016-0329-3
|View full text |Cite
|
Sign up to set email alerts
|

The Year of the Wisent

Abstract: Delving into European prehistory, two recent studies analyze ancient DNA from bison species depicted by our ancestors on the walls of their caves. The DNA tells a story of migrations driven by climate change but leaves some mystery clouding the genetic descent and climate preference of the still-extant wisent, otherwise known as the European bison.See research articles: https://bmcbiol.biomedcentral.com/articles/10.1186/s12915-016-0317-7 http://www.nature.com/articles/ncomms13158

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The first explanation (introgression) is most common for nuclear sister species with divergent mtDNA 4 , 12 . In this study, we test whether the anomalous mtDNA divergence of the closely related wisent and bison 13 originated as a result of ancient introgression or ILS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first explanation (introgression) is most common for nuclear sister species with divergent mtDNA 4 , 12 . In this study, we test whether the anomalous mtDNA divergence of the closely related wisent and bison 13 originated as a result of ancient introgression or ILS.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the wisent and American bison are morphologically similar and cross-fertile and have closely related nuclear genes 17 , 18 , but the mtDNA phylogeny consistently clusters the wisent with the lineage leading to taurine cattle and zebu 19 . Recently, this has been studied in more detail on the basis of ancient DNA and/or whole-genome sequences (WGS) 13 . Wecek et al 20 and Gautier et al 21 found that a small but variable part of the wisent genome originated from domestic cattle.…”
Section: Introductionmentioning
confidence: 99%
“…This situation was achieved only around 2016 when the genome of the extant B. bonasus (wisent) was sequenced [7,8], partial genomic information from historical specimens was obtained [9] and ancient Bison specimens from the Upper Pleistocene and the Holocene in Eurasia yielded sequencing results [10][11][12]. As a consequence, 2016 was declared the year of the wisent [13]. Likewise, in 2017, paleogenetic data focusing on the evolution of the B. priscus lineage in the American continent were produced [1].…”
Section: Introductionmentioning
confidence: 99%
“…), goat (Capra hircus) and sheep (Ovis aries). We also find reads classified as wisent (Bison) and buffalo (Bubalus), however, both species and their geographical distribution in this area remains debated (34)(35)(36)(37) (38)(39)(40), and reads could likely be missing or represent past genetic diversity from the taurine cattle found in the same layers. We therefore extracted all reads classified to each genus and blasted these against the nucleotide database (NCBI, RefSeq databases) using blastn (41) (see Methods).…”
Section: Animal Dnamentioning
confidence: 83%